DYNAMICS OF RADIOGENIC CHANGES IN THE INTENSITY OF LIPID PEROXIDATION PROCESSES IN THE BLOOD OF ANIMALS UNDER DIFFERENT MODES OF IRRADIATION - Petryna, L. G.; Moiseienko, M. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Experimental studies were performed on male Wistar rats. Single exposure of animals at doses of 1.0, 5.0, and 9.0 Gy was performed from a source with dose rates of 0.001, 0.01 0.1, and 1.0 Gy/min. The content of diene conjugates was determined at 0.5, 1, 2, 4, 6, 8, 10, 15, 20, and 30 days after exposure. It was found that the content of diene conjugates of blood varied wavy. The relative change in early products per 1 Gy irradiated at doses of 5.0 and 9.0 Gy was 1.5-2.0 and 4-5 times lower, respectively, than in animals irradiated at dose 1.0 Gy. After 4, 6, 8, 10 days, a clear dependence of the indicator on the magnitude of the radiation dose rate was not observed. The dynamics of accumulation of early LPO R products in the blood of rats, irradiated over a wide range of doses and capacities, indicates the nature of the development or inhibition of free radical oxidation processes.